Metachronous breast neoplasms: squamous cell carcinoma and lobular carcinoma in situ within a fibroadenoma - Moreno, Marcelo; Menegassi, Jerso; Zandavalli Neto, Oswaldo Valentim; Pauletto, Maiane Maria; Meurer, Franciele (Mastology, 2020)
Breast squamous cell carcinoma are rare, occurring in less than 0.1% of all breast carcinomas. This report describes the oncological conduct performed on a patient with a triple negative squamous cell carcinoma in the upper outer quadrant of the right breast. The same patient presented a lobular carcinoma in situ within a fibroadenoma of the contralateral breast, during the follow up period. The association of these two diseases in the same patient has not yet been described in the literature.